Critical stress level causing rock failure: a case study of Melamchi tunnel from central Nepal Himalaya - Shrestha, G. L.; Broch, E. (Journal of Nepal Geological Society, 2006)
The determination of critical stress level is important in tunnel stability assessment. In this paper, the results of laboratory test on rock samples from the proposed Melamchi tunnel alignment in central Nepal are presented. In order to determine the critical stress level, creep tests were carried out on the gneissic rock cores. Time-dependent deformation curves were used to estimate the steady-state deformation rate for a given constant stress level. The creep test curves were fitted with Burger's model and the rheological parameters were calibrated as suggested by previous researchers. Tunnel deformations were calculated for various time periods at a given stress level. On the basis of the creep test results at various uniaxial stress levels at constant temperature, an equation is given for the relationship between the strain rate and stress level.